Effects of Nordic hamstring exercise on hamstring injuries in high school soccer players: A randomized controlled trial - Hasebe, Y.; Akasaka, K.; Otsudo, T.; Tachibana, Y.; Hall, T.; Yamamoto, M. (International Journal of Sports Medicine, 2020)
We evaluated a range of physical characteristics related to hamstring injuries, as well as the Nordic Hamstring Exercise compliance rate, and whether this influenced the rate hamstring injury. Subjects comprised 259 male soccer players from seven high schools randomly clustered into two groups, a Nordic Hamstring Exercise group and a control group. Training and match time were logged, as well as details of hamstring injury, and subsequent time lost to hamstring injury recorded over a period of 27 weeks. The Nordic Hamstring Exercise compliance rate, injury rate per 10000 playing hours and time-lost-to-sport-injury rate were calculated. The relative risk and hamstring injury severity were also calculated. The hamstring injury rate was 1.04/10?000 h in the control group and 0.88/10?000 h in the intervention group. The relative risk for hamstring injury was 1.14. The time-lost to injury rate was 1116.3/10?000 h in the control group and 113.7/10?000 h in the intervention group; with relative risk 9.81. The Nordic Hamstring Exercise in high school soccer players significantly reduced hamstring injury severity compared to a control intervention. Our results indicate that the time-lost to injury rate should be taken into account when analyzing the severity of hamstring injury.